Instrument-Free Point-of-Care Diagnostic for Leishmania Parasites - Taralyn J. Wiggins; Ruonan Peng; Ruth V. Bushnell; John K. Tobin; David A. MacLeod; Ke Du; Gregory J. Tobin; Stephen J. Dollery (Diagnostics)
Background/Objective: Leishmaniasis is the second deadliest parasitic disease in the world, after malaria, with an estimated 1.6 million new cases each year. While cutaneous leishmaniasis can result in permanent scars from lesions after treatment, the mucocutaneous and visceral diseases can result in life-altering and life-threatening complications. Accurate species diagnosis is critical for treatment and follow-up, and while PCR-based diagnostics can provide sensitive parasite detection and species identification, they are slow, expensive, and not suitable for low-resource settings. In this publication, we describe our efforts to develop a simple, affordable, and instrument-free Leishmania DNA diagnostic that can be used in both high-tech settings and the field. Methods: Computational biology was utilized to design region-targeted RPA oligos and the corresponding CRISPR guides for the detection of all Leishmania species as well as the specific identification of L. (V.) panamensis as a predictor of mucocutaneous disease. Then, we executed systematic approaches for parasite lysis, RPA amplification of DNA, and fluorescent CRISPR crRNA detection. Results: We have demonstrated the ability to detect single-digit parasites without compromising the specificity in identifying single species as the proof of concept for a point-of-care diagnostic. Individual assays were carried out in succession, culminating in an unquenched fluorescent signal quantifiable over negative control. Conclusions: The described work is the foundation which will be implemented into a three-track [all Leishmania, mucocutaneous or visceral only, and a human positive control] assay that we plan to utilize in a Funnel Adapted Sensing Tube (FAST) single use, instrument-free, and affordable diagnostic.